An IOT architecture for counting people - BOTLER, Léo Happ (2017)
Knowing whether a room is occupied or not is crucial for improving electrical energy efficiency. For instance, if a given room is empty there is usually no need for the lights to be turned on. Usually in small spaces such as elevator halls, a Passive Infrared (PIR) sensor is used together with the lighting, but as it lacks accuracy, people often are left in the dark after a few minutes. Another factor that deteriorates energy efficiency is that these sensors are seldom connected to a network, limiting the application scenarios to simple tasks, such as controlling lamps. The same data could be used to improve other services such as adjusting the temperature of an air conditioner, which usually has a high impact on energy costs in countries with warm weather. In the present dissertation a wireless device capable of counting people in a room is implemented using Infrared (IR) Light Emitting Diode (LED)s. The implemented device is analyzed regarding energy consumption, cost, error count and installation time. It is also compared to other existing solutions. An architecture for interfacing this device with the Internet of Things (IoT) is provided as well as some of its applications in real scenarios. The results show that the architecture provided as well as the device implemented are useful in the presented scenarios, presenting a distance range of up to 30cm, a false negatives percentual error around 4% and an energy consumption of 1.519W.